(untitled) (Orfeu, 2025)
In this paper I’ve studied a few aspects of the production of the Pelotas born composer Luiz Carlos Lessa Vinholes, the first Brazilian composer to produce aleatoric works, comparing then with similar aspects of the production of the North-American composer John Cage, such as his initiative to create new theories for music structuring based in the rhythm, the use of the silence in his works and his option for a poetics aiming the indetermination in music, in order to understand the position of Vinholes in the sphere of the production of the aleatory music from the beginning of the decade of 1960. The article detects important points of divergence in both poetics, demonstrating that the Vinholes’ approach, apparently correlated to the Cage’s, differs a lot from it.